Encyclopedia of Signaling Molecules (Springer International Publishing, 2018)
The second edition of this encyclopedia presents about 1000 chapters and includes thousands of biologically important signaling molecules and the content is built on the core concepts of their functions along with early findings written by some of the world's foremost experts. The molecules are described by recognized leaders in each molecule. The interactions of these single molecules in signal transduction networks will also be explored. This encyclopedia marks a new era in overview of current cellular signaling molecules for the specialist and the interested non-specialist alike. Currently, there are more than 30,000 genes in human genome. However, not all the proteins encoded by these genes work equally in order to maintain homeostasis. Understanding the important signaling molecules as completely as possible will significantly improve our research -based teaching and scientific capabilities.